"Drinking Too Much, Fighting Too Much": The Dual "Disasters" of Intimate Partner Violence and Alcohol Use in South Africa. (August 2022) - Backe, Emma L.; Bosire, Edna; Mendenhall, Emily
The intersecting issues of intimate partner violence (IPV) and alcohol abuse in South Africa are often characterized as "disasters." Ethnographic research among women in Soweto demonstrates the different manifestations of IPV, perceptions of abuse, and coping mechanisms to manage harmful domestic relationships. Findings suggest a consistent relationship between excessive drinking patterns and IPV—most significantly, physical and emotional abuse—while indicating that domestic violence measures should include questions about stress. The authors also argue against pathologizing the relationship between IPV and alcohol abuse, to instead center the structured, sedimented ways that violence within the home has become a "normalized" disaster.